Penggunaan Media Video Pembelajaran Dalam Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas II-B SDN 5 Menteng Kota Palangka Raya - Lia Wulandari, Wulan; Azahari, Abd Rahman; Widya Permata, Femmy (PGSD FKIP UPR, 2025)
Based on initial observations before conducting the research, the researcher found that the lack of student interest and understanding in the learning material was due to the uninteresting learning process. This resulted in low learning outcomes for the second-grade students at SDN 5 Menteng, especially in multiplication mathematics content.The method used in this study is classroom action research. It is characterized by cycles consisting of planning, action implementation, observation, and reflection stages. The subjects of this study were 30 second-grade students at SDN 5 Menteng. Data collection techniques in this study included tests and observations. To determine the students' learning outcomes, multiple-choice questions with a maximum score of 100 were used, and data collection utilized observation sheets to gather data on teacher and student activities during the learning process.Based on the calculation of the average Pre-Test score, it was 53.3, categorized as not meeting the passing criteria, with a class completeness rate of 13.3%. The results in the first cycle showed that the average student learning outcomes increased to 72.9, meeting the passing criteria, and the class completeness rate also increased to 56.7%. In the second cycle, the average student learning outcomes further increased to 85.3, meeting the passing criteria, with a class completeness rate of 93.3%. Based on these results, it can be concluded that the application of educational video media in multiplication mathematics content can improve learning outcomes and make the learning process better.